"Dialogue" between Caco-2 and DCs regulated by Ganoderma atrum polysaccharide in intestinal-like Caco-2/DCs co-culture model. (June 2021) - Wang, Yudan; Ding, Xiaomeng; Chen, Yi; Xie, Jianhua; Zheng, Bing; Chang, Xinxin; Liu, Shiqi; Hu, Xiaobo; Yu, Qiang
Graphical abstract: Highlights: RNA-seq analysis found out 452 DEGs between PSG-1 and control group. NF-κB and TNF-α were among top 20 enriched pathways identified by KEGG. Cytokines and chemokines of DCs treated by TNF-α and NF-κB inhibitor were reduced. Adding TNF-α and NF-κB inhibitors depressed NF-κB and MAPK pathways of DCs. PSG-1 indirectly regulated DCs through TNF-α and NF-κB signaling pathways on Caco-2. Abstract: The previous research has indicated that Ganoderma atrum polysaccharide (PSG-1) indirectly affects the immune function of dendritic cells (DCs) in intestinal-like Caco-2/DCs co-culture model, in which NF-κB and MAPK pathway play an essential role. To explore the interaction of Caco-2 in the interaction between the intestinal epithelium and its internal immune cells, the intestinal-like Caco-2/DCs co-culture model was developed. All transcripts of Caco-2 treated with or without PSG-1 were globally screened by RNA-seq. The expression of 452 genes regulated by PSG-1 was statistically significant, the counts of up-regulated and down-regulated genes were 198 and 256, respectively. According to KEGG analysis, tumor necrosis factor (TNF)-α and NF-κB signaling pathways of Caco-2 were selected to elucidate the mechanism of interaction between Caco-2/DCs induced by PSG-1. After the addition of TNF-α inhibitor Apremilast and NF-κB inhibitor BAY11-70821 in Caco-2, expression of cytokines (TNF-α, IL-6, IL-1β, IL-10), chemokines (RANTES, MIP-1α, MCP-1), and the key proteins of MAPK and NF-κB pathways of DCs were all reduced. In summary, "dialogue" between Caco-2 and DCs was regulated by PSG-1 through TNF-α and NF-κB signaling pathways of Caco-2 in the model.